2002
DOI: 10.1021/jp0134401
|View full text |Cite
|
Sign up to set email alerts
|

Deposition of Barium Titanate Films on Silicon by Barium Fluotitanate Powder

Abstract: In this study, the barium fluotitanate powder prepared by the precipitate of hexafluorotitanic acid and barium nitrate solution was used as the precursor for the deposition of barium titanate film on silicon substrate. The boric acid was incorporated into the deposition solution to enhance the deposition rate. A mirrorlike film can be obtained. The chemical reaction of liquid-phase deposited barium titanate is proposed. The leakage current density is as low as 5 × 10 -9 A/cm 2 . The dielectric constant and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Barium titanate, BaTiO 3 (BTO), is not only one of the most important ferroelectric material utilized for ceramic capacitors, ferroelectric random access memory, and piezoelectric devices 1, 2, but also an important dielectric material from a technological standpoint due to its extremely high electrical permittivity. The surface structure as well as the electronic properties has a very important effect on the applications of BTO in the fields of thin films and catalysts 3, 4. Among all the orientations of the BTO crystal, the (100) surface 5–7 was the most extensively studied owing to its nonpolar characteristic and high stability.…”
Section: Introductionmentioning
confidence: 99%
“…Barium titanate, BaTiO 3 (BTO), is not only one of the most important ferroelectric material utilized for ceramic capacitors, ferroelectric random access memory, and piezoelectric devices 1, 2, but also an important dielectric material from a technological standpoint due to its extremely high electrical permittivity. The surface structure as well as the electronic properties has a very important effect on the applications of BTO in the fields of thin films and catalysts 3, 4. Among all the orientations of the BTO crystal, the (100) surface 5–7 was the most extensively studied owing to its nonpolar characteristic and high stability.…”
Section: Introductionmentioning
confidence: 99%
“…The interesting stoichiometric composition of our films is significant because it makes it possible to avoid the problematic effects of nonstoichiometry on the dielectric properties. Comparably, Lee et al has reported direct deposition of a thin film containing Ba, Ti, and O by the LPD method using an aqueous solution of barium fluorotitanate . However, the chemical composition of the film was nonstoichiometric, typically Ba/Ti/O 1:10.9:16.5 …”
Section: Introductionmentioning
confidence: 99%
“…Previous attempts, by Lee et al, at utilizing the BaTiF 6 single-source molecular precursor to make BaTiO 3 films by an elevated temperature liquid phase deposition method resulted in nonstoichiometric (ca. 1:11 Ba/Ti) and amorphous thin films . Thus, it appears that the unique combination of the silicatein biocatalyst with BaTiF 6 leads to the formation of the high-temperature crystalline perovskite-like phase at low temperature, in which the 1:1 stoichiometry between barium and titanium is maintained.…”
Section: Discussionmentioning
confidence: 99%
“…Tris·HCl (tris(hydroxymethyl)aminomethane hydrochloride, 99+%), hexafluorotitanic acid (99.9%), and barium nitrate (99.999%) were purchased from Aldrich and used without further purification. The barium fluorotitanate (BaTiF 6 ) precursor was prepared according to literature procedure and isolated as a white microcrystalline solid . The identity of the microcrystalline solid was confirmed by powder X-ray diffraction (XRD).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation